Disambiguating auditory information causes priming, but not aftereffects, in the perception of ambiguous faces. (May 2018) - Jon, Olivia; Walsh, Jennifer A.; Benarroch, Miriam F.F.; Wade, Trevor; Lipman, Corey; Greenberg, Emma; Rutherford, M.D.
Highlights: Providing a disambiguating story for surprise face lead to priming not aftereffects. Priming was not disrupted by a model change from prime to probe images. Priming was not disrupted by stimulus asynchrony. Attempts to disambiguate gender-ambiguous faces yielded no measurable effect. The top-down influence on face perception was cross-modal. Abstract: In five experiments, we used a visual aftereffects paradigm to probe whether emotion- and gender-relevant information presented in the auditory domain would affect the formation of visual aftereffects or would instead create a priming effect. In experiment 1, participants fixated on surprise facial expressions while listening to a story that described the surprise as either happy or sad, and then were asked to classify the expression of a briefly presented neutral face. Subsequently, the identity of the model (experiment 2) and the timing of the auditory presentation (experiment 3) were manipulated. In experiment 4, this approach was extended to judgments of gender. Experiment 5 serves as a control experiment in which the story, but no visual stimuli, was presented during the adaptation phase. In each case results revealed evidence of priming, but no evidence that information in the auditory domain affected the formation of aftereffects.